0120 Simethics: Teaching medical ethics through high-fidelity simulation. (2nd November 2015) - Collins, Sandra; Crowther, Nicola; McCabe, Anne; Natarajan, Michael; Jones, Kevin
Abstract : Background: Effective management of clinical ethical issues has a significant impact on patients' experience and outcome. Our anonymous survey found that final year medical students have a confidence of 5.6 (10-point Likert scale) of the management of common clinical medical ethical issues. We have designed high-fidelity simulation teaching to teach about ethical principles and their practical application to patient cases. Methodology: We identified three common clinical ethical issues through focus group work with junior doctors. We designed three high-fidelity simulation scenarios to cover the issues. The scenarios were; (1) maintaining patient confidentiality when talking to relatives, (2) mental capacity assessment in a self-discharge case and (3) acting in a vulnerable patient's best interests. We delivered the three scenarios with detailed debriefs to five groups of final year medical students. Results: Thirty-three medical students provided feedback (n = 33) through an anonymous paper questionnaire. We collected qualitative and quantitative feedback via fre text boxes and 10-point Likert scales. Confidentiality: After the confidentiality scenario there was an improved awareness of 1.38/10 (p-value 0.0007) from 8.21 to 9.59. There was an improvement in confidence with management of 2.36/10 (p-value <0.0001) from 5.97 to 8.33. Capacity: This scenario showed an improved perceived relevance of 1.01/10 (p-value 0.0015) from 8.58 to 9.59. Student's confidence with management improved by 1.94/10 (p-value < 0.0001) from 6.70 to 8.64. Best interests: Students reported an improved awareness of 1.03/10 (p-value < 0.0052) from 8.58 to 9.61. The student's confidence with management improved by 2.30/10 (p-value < 0.0001) from 5.97 to 8.27. Students commented in the feedback that there was a 'massive difference to learning in real time than textbook' and it made the ethics teaching 'much more fun and more memorable.' Recommendations: We hope to expand this teaching to students within other healthcare professions and postgraduate healthcare professionals.